Cost-Effectiveness Analysis of Six Immunotherapy-Based Regimens and Sunitinib in Metastatic Renal Cell Carcinoma: A Public Payer Perspective. Issue 3 (4th March 2023) - Yoo, Minkyoung; Nelson, Richard E.; Cutshall, Zachary; Dougherty, Maura; Kohli, Manish
Abstract : PURPOSE: Several new treatment combinations have been approved in metastatic renal cell carcinoma (mRCC). To determine the optimal therapy on the basis of cost and health outcomes, we performed a cost-effectiveness analysis of approved immunotherapy-tyrosine kinase inhibitor/immunotherapy drug combinations and sunitinib using public payer acquisition costs in the United States. METHODS: We constructed a decision model with a 10-year time horizon. The seven treatment drug strategies included atezolizumab + bevacizumab, avelumab + axitinib, pembrolizumab + axitinib, nivolumab + ipilimumab (NI), nivolumab + cabozantinib, lenvatinib + pembrolizumab, and sunitinib. The effectiveness outcome in our model was quality-adjusted life-years (QALYs) with utility values on the basis of the published literature. Costs included drug acquisition costs and costs for management of grade 3-4 drug-related adverse events. We used a partitioned survival model in which patients with mRCC transitioned between three health states (progression-free, progressive disease, and death) at monthly intervals on the basis of parametric survival function estimated from published survival curves. To determine cost-effectiveness, we constructed incremental cost-effectiveness ratios (ICERs) by dividing the difference in cost by the difference in effectiveness between nondominated treatments. RESULTS: The least expensive treatment was sunitinib ($357, 948 US dollars [USD]-$656, 100 USD), whereas the most expensive was either lenvatinib + pembrolizumab or pembrolizumab + axitinib ($959, 302 USD-$1, 403, 671 USD). NI yielded the most QALYs (3.6), whereas avelumab + axitinib yielded the least (2.5). NI had an incremental ICER of $297, 465 USD-$348, 516 USD compared with sunitinib. In sensitivity analyses, this ICER fell below $150, 000 USD/QALY if the initial 4-month cost of NI decreased by 22%-38%. CONCLUSION: NI was the most effective combination for mRCC, but at a willingness-to-pay threshold of $150, 000 USD/QALY, sunitinib was the most cost-effective approach.